A cross sectional preliminary study on the prevalence of ABO and rhesus blood groups in Bani Waleed City, Libya - Ameigaal, Samira; Ageel, Ahmed (Libyan International Medical University Journal, 2019)
Background: The distribution of ABO and rhesus (Rh) blood groups has been reported to be different in several world populations. There have been few studies about blood groups among Libyan population. Aims: The study aims to determine the distribution and frequency of ABO and Rh blood groups among Libyan population in Bani Waleed city. Subjects and Methods: The study group had included 344 participants of both genders aged between 15 and 80 years. Blood samples were collected for ABO and Rh blood group analysis from September to December 2018. Results: The percentage of male participants was 55.8% and 48.2% were female. The highest percentage (30.2%) were among the age group of 23–32 years. O blood group was the most common (43.6%), followed by A (31.7%), B (17.7%), and finally, AB blood group (7.0%). The percentage of Rh positive (Rh+) was 72.2% and of Rh negative (Rh−) was 23.8%. Moreover, the prevalence of ABO with Rh+ was 33.4%, 27.6%, 11.3%, and 4.7% for O+, A+, B+, and AB+, respectively. The prevalence of ABO with Rh− was 9.9%, 6.11%, 4.1%, and 2.6% for O−, B−, A−, and AB−, respectively. Conclusion: The distribution of ABO blood group in the present study is ordered of O > A> B > AB with majority of Rh+ and higher frequencies of Rh−. The findings of this study will contribute in health services and use them as database to know detailed information of blood types such as for blood bank and blood transfusion and also to be used in population studies.
Keywords: ABO; Bani Waleed; blood groups; Libya; rhesus factor